Analysis of the Effects of Green Banking, Capital Adequacy Ratio on Profitability Growth with Institutional Ownership as a Moderating Variable - Rahmat, Ainul Yaqin Rahmat Daeng Marakka; Ulfi Kartika Oktaviana (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
The goal of this study is to examine a number of variables that can affect profitability growth, such as institutional ownership as a moderating component, green banking, and capital sufficiency. The study is a quantitative one that gathers secondary data from 11 Indonesian public Sharia banks' financial reports for the years 2018 to 2022. Panel data regression analysis is the method employed, and Excel and Eviews 12 are used as test tools. The study's findings indicate that all free variables have a limited interdependence. Modernizations like institutional ownership and green banking have no detrimental effects on profitability growth. The accessibility of capital and the institutional ownership that modernizes it have a profoundly positive impact on profitability growth.